Comparative analysis of left atrial size and appendage morphology in paroxysmal and persistent atrial fibrillation patients - J. Pongratz; L. Riess; S. Hartl; B. Brueck; C. Tesche; D. Olbrich; M. Wankerl; U. Dorwarth; E. Hoffmann; F. Straube (Journal of Arrhythmia, 2025)
Abstract Purpose Pulmonary vein isolation (PVI) is effective in treating atrial fibrillation (AF), but outcomes are worse for persistent AF (persAF) patients than paroxysmal AF (PAF) patients. The study aimed to identify differences in left atrial (LA) and left atrial appendage (LAA) anatomy in different AF types. Methods In a single‐center observational study, a blinded retrospective analysis of preprocedural cardiac computed tomography angiography (CCTA) images was performed. The study evaluated the dimensions of the LA and pulmonary veins (PV), as well as the size and morphology of the LAA using a 3D electroanatomical mapping system. Results Between 2012 and 2016, a total of 1103 patients underwent second‐generation cryoballoon PVI. Of these, 725 patients (65.7%) had CCTA available, and 473 of these (65.2%) had sufficient quality for measurements. The mean age of the patients was 66.3 ± 9.5 years, and PAF was present in 277 (58.6%) participants. The study found that in persAF patients, LA dimensions such as LA volume [mL] (108; 125; p < .001) or PV ostial dimensions were significantly larger than in those with PAF. LAA volume [mL] (8.3; 9.2; p = .005) and LAA ostial area [mm2] (325; 353; p = .01) were enlarged in persAF. There were no significant differences regarding LAA morphology, with the overall distribution being “windsock” (51%), “chicken‐wing” (20%), “cauliflower” (15%), and “cactus” (13%). Conclusion Compared to PAF, persAF patients had significantly larger LA as well as LAA dimensions. LAA morphological types were distributed equally in both groups suggesting that LAA morphology may not be associated with the underlying AF type.